2016
DOI: 10.3389/fonc.2016.00114
|View full text |Cite
|
Sign up to set email alerts
|

Intensity-Modulated Radiation Therapy with Stereotactic Body Radiation Therapy Boost for Unfavorable Prostate Cancer: The Georgetown University Experience

Abstract: Purpose/objective(s)Stereotactic body radiation therapy (SBRT) is emerging as a minimally invasive alternative to brachytherapy to deliver highly conformal, dose-­escalated radiation therapy (RT) to the prostate. SBRT alone may not adequately cover the tumor extensions outside the prostate commonly seen in unfavorable prostate cancer. External beam radiation therapy (EBRT) with high dose rate brachytherapy boost is a proven effective therapy for unfavorable prostate cancer. This study reports on early prostate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…One other strength of our series is the absence of ADT to preserve potency and QoL and to avoid metabolic dysfunction. In a retrospective series of 108 patients (45 with an intermediate-risk cancer), the majority of them received ADT [ 21 ]. Patients were treated with SBRT (19.5 Gy in three fractions) followed by fiducial-guided IMRT (45–50.4 Gy).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One other strength of our series is the absence of ADT to preserve potency and QoL and to avoid metabolic dysfunction. In a retrospective series of 108 patients (45 with an intermediate-risk cancer), the majority of them received ADT [ 21 ]. Patients were treated with SBRT (19.5 Gy in three fractions) followed by fiducial-guided IMRT (45–50.4 Gy).…”
Section: Discussionmentioning
confidence: 99%
“…Erectile dysfunction was not assessed. At 2 years 13.7% and 5% of men complained from moderate to severe urinary and bowel dysfunctions respectively [ 21 ]. Another series reported results of SBRT as a boost after pelvic EBR in patients with high-risk prostate carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to maximize the benefit of administering high doses per fraction and patient acceptance, we have examined the use of stereotactic body radiation therapy (SBRT) as a prostatic boost to image-guided intensity-modulated radiation therapy (IMRT) for the treatment of patients with unfavorable clinically localized prostate cancer. Previously, we reported early outcomes of this treatment modality, with a 3-year biochemical-free survival rate of 100% for intermediate-risk and 89.8% for high-risk disease ( 19 ). Similarly, we reported that such a therapy conferred minimal impact on long-term quality of life (QOL) ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Volume delineation of the prostate and seminal vesicles was defined using registration of the pretreatment magnetic resonance image (MRI) with the pretreatment CT simulation. Treatment‐planning details of prostate SBRT alone as well as external‐beam radiotherapy (EBRT) plus SBRT boost (intensity‐modulated radiotherapy [IMRT] plus SBRT boost) have been previously described . The prescribed dose was 35 to 36.25 grays (Gy) in 5 fractions for SBRT.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment-planning details of prostate SBRT alone as well as external-beam radiotherapy (EBRT) plus SBRT boost (intensity-modulated radiotherapy [IMRT] plus SBRT boost) have been previously described. 14,15 The prescribed dose was 35 to 36.25 grays (Gy) in 5 fractions for SBRT. Certain patients with higher risk disease received IMRT plus SBRT boost, with the prescribed dose including IMRT at 45 to 50.4 Gy in 1.8-Gy fractions plus SBRT at 19.5 Gy in 3 fractions.…”
Section: Treatmentmentioning
confidence: 99%